2013
DOI: 10.1097/bot.0b013e3182691288
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Molecular and Biologic Characterization of Biomembrane Formation Adjacent to a Methacrylate Spacer in the Rat Femoral Segmental Defect Model

Abstract: This rat bone model was effective in creation of the biomembrane. Bone and cartilage foci were formed within the vascularized biomembrane with associated expression of genes critical for bone and cartilage development/formation and vascularization. The polymethyl methacrylate-induced biomembrane offers an exciting potential solution for segmental defects; the biomembrane, may act as a receptive bed and also serve as a source for mesenchymal stem cells, which could be recruited/directed for the healing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 19 publications
3
57
0
2
Order By: Relevance
“…As has been noted in basic science studies 21,22 and some case studies, 24 mineralized tissue will sometimes extend from the original cortical bone ends to encase the spacer. There were no differences between groups in maximal bone extent length (~1.7mm) or total bone volumes.…”
Section: Resultsmentioning
confidence: 95%
“…As has been noted in basic science studies 21,22 and some case studies, 24 mineralized tissue will sometimes extend from the original cortical bone ends to encase the spacer. There were no differences between groups in maximal bone extent length (~1.7mm) or total bone volumes.…”
Section: Resultsmentioning
confidence: 95%
“…Other studies have characterized the induced membrane formed by PMMA in rat models . There are clear similarities between human and rat induced membrane with respect to timing of membrane formation, histological composition including osteoprogenitor cells, and presence of important growth factors such as transforming growth factor‐beta (TGF‐β), bone morphogenetic protein‐2 (BMP‐2), and vascular endothelial growth factor (VEGF) .…”
Section: Discussionmentioning
confidence: 99%
“…This is an important finding in human biomembrane research and is similar to previous studies from our laboratory that have evaluated the properties of biomembranes formed in a rat segmental defect model. 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…Results from age- and site-controlled small animal studies were previously reported by our group. 24,25 Another limitation of this study is that it has a relatively small sample size for the gene expression analyses. Although many of the differences in gene expression reached statistical significance, future studies with larger sample sizes are needed.…”
Section: Discussionmentioning
confidence: 99%